中国传统文化传播视域下朱子理学在印尼孔教中的本土传播路径 The Localization Pathways of Zhu Xi's Neo-Confucianism in Indonesian Confucianism within the Context of Traditional Chinese Cultural Diffusion - Siem Hong Hun (Asosiasi Program Studi Mandarin Indonesia, 2025)
摘要作为中国传统文化的软实力，朱子理学在印尼具有重要影响，理应促进其广泛传播。本文通过分析六本印尼中学（7至12年级）官方孔教与道德伦理教科书，结合印尼孔教的发展历程，探讨朱子理学在印尼的本土化传播路径。研究发现朱子理学核心价值与印度尼西亚建国五大原则潘查希拉高度契合；能以孔教一体以宗教形式继续在印尼发扬光大，通过宗教制度化、教育化传承及社会功能化进行本土化传播，不仅能够为朱子学在印尼的本土化发展提供坚实支撑，也将从整体上推动儒家思想的国际传播走向更加稳健与可持续的发展道路。关键词：文化传播，朱子理学，印尼孔教，本土化 AbstractAs a soft power of traditional Chinese culture, Zhu Xi's Neo-Confucianism holds significant influence in Indonesia and should be promoted for wider spread. This paper analyzes six official Confucianism and Ethics textbooks used in Indonesian secondary schools (grades 7–12), combining them with the developmental history of Confucianism in Indonesia to explore the localized diffusion pathways of Zhu Xi's Neo-Confucianism in the country. Research reveals that the core values of Zhu Xi's Neo-Confucianism align closely with Indonesia's Pancasila, the five founding principles of the nation. By taking form as Khonghucu religion, its influence could continue to flourish through religious institutionalization, educational transmission, and social functionalization, hence not only provides a solid foundation for the localized development of Zhu Xi's Neo-Confucianism in Indonesia, but also propels the international spread of Confucian thoughts toward a more stable and sustainable path.Keywords: cultural diffusion， Zhu Xi's Neo-Confucianism;，Indonesian Khonghucu， localization